Deconjugation of soy isoflavone glucuronides needed for estrogenic activity. Issue 4 (June 2015) - Islam, M.A.; Bekele, R.; vanden Berg, J.H.J.; Kuswanti, Y.; Thapa, O.; Soltani, S.; van Leeuwen, F.X.R.; Rietjens, I.M.C.M.; Murk, A.J.
Highlights Genistein and diadzein glucuronides (GG and DG) are not estrogenic. Deconjugation of GG and DG to their corresponding aglycones renders them estrogenic. The slight estrogenic activity of GG and DG in vitro is the result of intracellular deconjugation. At realistic plasma concentrations of the SIF breast cancer cell proliferation was inhibited. Deconjugation of GG and DG by rat S9 is 30 times faster than by human breast tissue S9.